COVID-19 vaccine uptake and effectiveness in adults aged 50 years and older in Wales UK: a 1.2m population data-linkage cohort approach. Issue 1 (31st December 2022) - Perry, Malorie; Gravenor, Michael B; Cottrell, Simon; Bedston, Stuart; Roberts, Richard; Williams, Christopher; Salmon, Jane; Lyons, Jane; Akbari, Ashley; Lyons, Ronan A; Torabi, Fatemeh; Griffiths, Lucy J
ABSTRACT: Vaccination programs against COVID-19 vary globally with estimates of vaccine effectiveness (VE) affected by vaccine type, schedule, strain, outcome, and recipient characteristics. This study assessed VE of BNT162b2 and ChAdOx1 vaccines against PCR positive SARS-CoV-2 infection, hospital admission, and death among adults aged 50 years and older in Wales, UK during the period 7 December 2020 to 18 July 2021, when Alpha, followed by Delta, were the predominant variants. We used individual-level linked routinely collected data within the Secure Anonymized Information Linkage (SAIL) Databank. Data were available for 1, 262, 689 adults aged 50 years and over; coverage of one dose of any COVID-19 vaccine in this population was 92.6%, with coverage of two doses 90.4%. VE against PCR positive infection at 28-days or more post first dose of any COVID-19 vaccine was 16.0% (95%CI 9.6–22.0), and 42.0% (95%CI 36.5–47.1) seven or more days after a second dose. VE against hospital admission was higher at 72.9% (95%CI 63.6–79.8) 28 days or more post vaccination with one dose of any vaccine type, and 84.9% (95%CI 78.2–89.5) at 7 or more days post two doses. VE for one dose against death was estimated to be 80.9% (95%CI 72.1–86.9). VE against PCR positive infection and hospital admission was higher for BNT162b2 compared to ChAdOx1. In conclusion, vaccine uptake has been high among adults in Wales and VE estimates are encouraging, with two doses providing considerable protection against severe outcomes. Continued roll-out of the vaccination programme within Wales, and globally, is crucial in our fight against COVID-19.